Effects of two different anesthetic protocols on 64‐MDCT coronary angiography in dogs. Issue 1 (26th July 2014) - Drees, Randi; Johnson, Rebecca A.; Pinkerton, Marie; Del Rio, Alejandro Munoz; Saunders, Jimmy H.; François, Christopher J.
<x xml:space="preserve">Abstract</x> Heart rate is a major factor influencing diagnostic image quality in computed tomographic coronary artery angiography (MDCT‐CA), with an ideal heart rate of 60–65 beats/min in humans. The purpose of this prospective study was to compare effects of two different clinically applicable anesthetic protocols on cardiovascular parameters and 64‐MDCT‐CA quality in 10 healthy dogs. Scan protocols and bolus volumes were standardized. Image evaluations were performed in random order by a board‐certified veterinary radiologist who was unaware of anesthetic protocols used. Heart rate during image acquisition did not differ between protocols (P = 1), with 80.6 ± 7.5 bpm for protocol A and 79.2 ± 14.2 bpm for protocol B. Mean blood pressure was significantly higher (P > 0.05) using protocol B (protocol A 62.9 ± 9.1 vs. protocol B 72.4 ± 15.9 mmHg). The R‐R intervals allowing for best depiction of individual coronary artery segments were found in the end diastolic period and varied between the 70% and 95% interval. Diagnostic quality was rated excellent, good, and moderate in the majority of the segments evaluated, with higher scores given for more proximal segments and lower for more distal segments, respectively. Blur was the most commonly observed artifact and mainly affected the distal segments. No significant differences were identified between the two protocols for optimal reconstruction interval, diagnostic quality and measured length individual segments, or proximal diameter of the coronary arteries (P = 1). Findings indicated that, when used with a standardized bolus volume, both of these anesthetic protocols yielded diagnostic quality coronary 64‐MDCT‐CA exams in healthy dogs.